Seasonal variations in water quality and major threats to Nellore Cheruvu (tank), Nellore district, India - Sreenivasulu, K; Hossain, Kaizar; Damodharam, T (International Journal of Environment, 2014)
Water is the most vital resource for the living beings to survive. India has a vast and varied inland water resource which is considered to be richest in world’s nature lakes. The physico-chemical characteristic of Nellore tank has been studied for monsoon, pre-monsoon, post-monsoon in the year. From the results water body was found to be well in the permissible limit of BIS (1998, except pH, DO, BOD and turbidity in some seasons, which may be due to anthropogenic activities in the area, and input of nutrients and other organic and inorganic substances through runoff water from agricultural fields. DOI: http://dx.doi.org/10.3126/ije.v3i2.10502 International Journal of the Environment Vol.3(2) 2014: 28-35